Skull diversity in the Homo lineage and the relative position of Homo naledi. Issue 104 (March 2017) - Schroeder, Lauren; Scott, Jill E.; Garvin, Heather M.; Laird, Myra F.; Dembo, Mana; Radovčić, Davorka; Berger, Lee R.; de Ruiter, Darryl J.; Ackermann, Rebecca R.
Abstract: The discovery of Homo naledi has expanded the range of phenotypic variation in Homo, leading to new questions surrounding the mosaic nature of morphological evolution. Though currently undated, its unique morphological pattern and possible phylogenetic relationships to other hominin taxa suggest a complex evolutionary scenario. Here, we perform geometric morphometric analyses on H. naledi cranial and mandibular remains to investigate its morphological relationship with species of Homo and Australopithecus . We use Generalized Procrustes analysis to place H. naledi within the pattern of known hominin skull diversity, distributions of Procrustes distances among individuals to compare H. naledi and Homo erectus, and neighbor joining trees to investigate the potential phenetic relationships between groups. Our goal is to address a set of hypotheses relating to the uniqueness of H. naledi, its affinity with H. erectus, and the age of the fossils based on skull morphology. Our results indicate that, cranially, H. naledi aligns with members of the genus Homo, with closest affiliations to H. erectus . The mandibular results are less clear; H. naledi closely associates with a number of taxa, including some australopiths. However, results also show that although H. naledi shares similarities with H. erectus, some distances from this taxon – especially small-brained members of this taxon – are extreme. The neighbor joining trees place H. naledi firmly within Homo . The trees based on cranial morphology again indicate a close relationship between H. naledi and H. erectus, whereas the mandibular tree places H. naledi closer to basal Homo, suggesting a deeper antiquity. Altogether, these results emphasize the unique combination of features ( H. erectus -like cranium, less derived mandible) defining H. naledi . Our results also highlight the variability within Homo, calling for a greater focus on the cause of this variability, and emphasizing the importance of using the total morphological package for species diagnoses.